EVALUASI EKSTRAKULIKULER MULTIMEDIA SEBAGAI PENUNJANG PEMBELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SD NEGERI KUMPULREJO 02 SALATIGA - Tegar Santoso, Yosafat; Tyas Asri Hardini, Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the implementation of the Multimedia extracurricular program as a support for Information and Communication Technology (ICT) learning at Kumpulrejo 02 Elementary School, Salatiga. The study uses a qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model to obtain a comprehensive picture of the planning, implementation, and results of the Multimedia extracurricular program. The research subjects include the principal, Multimedia extracurricular mentors, and students from grades I to VI who participate in extracurricular activities with a total of 113 students. Data collection techniques are carried out through observation, interviews, and document studies, while data analysis uses data reduction, data presentation, and drawing conclusions with triangulation of sources and techniques. The research results indicate that, in terms of context, the Multimedia extracurricular program was implemented based on the school's needs and aligned with the school's vision and mission in addressing technological developments in the digital era. In terms of input, human resources, facilities and infrastructure, and school policy support were deemed adequate, although there were still limitations in time management and optimal facility utilization. In terms of process, the extracurricular activities proceeded according to plan, with materials on the use of Microsoft Word and Canva applications through hands-on practice using Chromebook s. In terms of product, the Multimedia extracurricular program had a positive impact on improving students' basic ICT skills, creativity, and learning interests. Based on the evaluation results, the Multimedia extracurricular program was deemed worthy of continuation with improvements to enhance the program's effectiveness and sustainability.